Association Between Weight Gain From Young to Middle Adulthood and Metabolic Syndrome Across Different BMI Categories at Young Adulthood - Wang, Xiuling; Song, Jiali; Gao, Yan; Wu, Chaoqun; Zhang, Xingyi; Li, Teng; Cui, Jianlan; Song, Lijuan; Xu, Wei; Yang, Yang; Zhang, Haibo; Lu, Jiapeng; et al. (Frontiers in Endocrinology, 2022)
Objectives We aimed to assess the dose-response association between weight gain from young to middle adulthood and metabolic syndrome risk, across BMI categories at young adulthood. Methods Based on a national population-based screening project, middle-aged (35–64 years) participants who recalled weight at age 25 years and received standardized measurements were included. Multivariable adjusted restricted cubic splines and logistic regression models were applied. Results In total, 439 891 participants were included (62.0% women, 52.0 ± 7.6 years). Larger weight gain from young to middle adulthood was associated with higher metabolic syndrome risk at middle adulthood, with odds of 2.02 (1.99–2.06), 1.93 (1.92–1.94), 1.66 (1.64–1.69) per 5-kg weight gain across participants who were underweight, normal-weight and overweight/obese at young adulthood, respectively. After further adjusting for current body mass index (BMI), larger weight gain still correlated with higher metabolic syndrome risk among underweight and normal-weight participants, while an inverted U-shaped association was observed in overweight/obese participants. Conclusions Weight maintenance from young to middle adulthood could be effective to mitigate metabolic syndrome burden, especially among underweight and normal-weight people. Historical weight gain confers varied information about metabolic syndrome risk independent of attained BMI across BMI categories at young adulthood.